Materialism and Consumer Ethics: An Exploratory Study - Muncy, James A. (Journal of business ethics, 1998)
As the issue of marketing's social responsibility grows in significance, the topic of materialism surfaces. While many marketing efforts encourage materialism, the materialism that is encouraged may have negative societal effects. An understanding of the effects of materialism on individuals, families, society, etc., is important in evaluating whether or not it is socially irresponsible for marketers to encourage materialism. However, the adequate empirical work has not yet been done on the overall effects of materialism. The current paper asks and addresses one important empirical question in this area. Do consumers who are more materialistic have different ethical standards than those who are not? Empirical evidence is presented which would indicate that materialism is negatively correlated with people's higher ethical standards as consumers. The implications for this in understanding social responsibility are discussed.